2017
DOI: 10.1038/s41598-017-16446-7
|View full text |Cite
|
Sign up to set email alerts
|

Isochlorogenic acid C prevents enterovirus 71 infection via modulating redox homeostasis of glutathione

Abstract: Enterovirus 71 (EV71) is a key pathogen of hand, foot and mouth disease (HFMD) in children under 6 years of age. The antiviral potency of antioxidant isochlorogenic acid C (ICAC) extracted from foods was evaluated in cellular and animal models. First, the cytotoxicity of ICAC on Vero cells was investigated. The viral plaques, cytopathic effects and yield induced by EV71 infection were obviously reduced by ICAC, which was consistent with the investigation of VP1 transcripts and protein expression. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Strikingly, studies had shown that isochlorogenic acid B had a protective effect on liver fibrosis in mice with nonalcoholic steatohepatitis. And isochlorogenic acid C was found to prevent enterovirus 71 infection by regulating the redox homeostasis of glutathione [ 39 ]. Glycyrrhizic acid and protocatechualdehyde had been proven to have powerful antioxidant effects, which are considered to be promising potential human antiaging compounds [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, studies had shown that isochlorogenic acid B had a protective effect on liver fibrosis in mice with nonalcoholic steatohepatitis. And isochlorogenic acid C was found to prevent enterovirus 71 infection by regulating the redox homeostasis of glutathione [ 39 ]. Glycyrrhizic acid and protocatechualdehyde had been proven to have powerful antioxidant effects, which are considered to be promising potential human antiaging compounds [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cells contain glutathione in both reduced (GSH) and oxidised (GSSG) forms, whose balance is crucial for maintaining cellular redox potential 9 . Disruption of the GSH/GSSG balance is associated with several enterovirus infections, including EV-A71 10 , CV-A16 and CV-B3 11ā€“13 . Furthermore, depletion of GSH, using l -butathione sulfoximate (BSO) 14,15 and TP219 16 , blocks the assembly of protomeric units into pentamers 14,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…EV71 infection is strongly associated with severe HFMD, which is accompanied by neurological symptoms and usually leads to death. Therefore, many studies have focused on the identification of substances with activity against EV71, and these studies have identified many candidate drugs for the treatment of EV71 infection, such as amphotericin B, isochlorogenic acid C, acid betaā€glucosidase 1, sulfated rhamnan, and suramin . Considering their relatively low cytotoxicity, extracts from traditional Chinese medicines or foods show particular advantages and have attracted increasing attention …”
Section: Discussionmentioning
confidence: 99%